150 Gbps THz chipscale topological photonic diplexer - Gupta, Manoj (2024)
Photonic diplexers are being widely investigated for high data transfer rates in on-chip communication. However, dividing the available spectrum into nonoverlapping multicarrier frequency sub-bands has remained a challenge in designing frequency-selective time-invariant channels. Here, an on-chip topological diplexer is reported exhibiting terahertz frequency band filtering through Klein tunneling of topological edge modes. The silicon topological diplexer chip facilitates two high-speed channels with quadrature amplitude modulation (QAM) over a broad bandwidth of 12.5 GHz each. These channels operate at carrier frequencies of 305 and 321.6 GHz, achieving a combined diplexer capacity of 150 Gbit s-1 . To ensure minimal interference between adjacent channels, a guard band is implemented. Topologically protected edge modes suppress the frequency selective fading of the broadband signals and hold promise for diverse integrated photonic applications spanning terahertz and telecommunication realms, including the design of lossless topological multiplexers, interconnects, antennas, and modulators for the sixth to X generation (6G to XG) wireless.